Bibliometric Analysis of Evaluation in Physical Education: A Study Based on The Scopus Database From 2013 to 2023 - Sefri Hardiansyah; Nurlan Kusmaedi; Amung Ma'mun; Herman Subarjah (Journal of Innovation in Educational and Cultural Research, 2024)
Evaluation in physical education provides information about the extent to which physical education objectives have been achieved and ensures that all processes have been carried out correctly. This study aims to investigate trends in evaluation research in physical education based on the Scopus database from 2013 to 2023. This is expected to provide an overview of the latest developments in evaluation research in physical education and to illustrate future research opportunities. Based on a search of the Scopus database through the Publish or Perish application with two title words, "Evaluation in Physical Education" and "Evaluation in PE," 50 articles were found suitable for analysis using VOSviewer visualization. The analysis results show that the most publications on evaluation in physical education occurred in 2021, with nine articles. Meanwhile, the highest citation amounted to 122 citations in 2020. Based on the analysis that has been carried out using VOSviewer, it is obtained that the term "Evaluation in Physical Education" or "Evaluation in PE" is still rarely discussed in academic literature; therefore, research on evaluation in physical education in the future has the potential to be carried out as an effort to ensure the quality of physical education learning.